Strategic management of financial security in the system of ensuring Ukraine’s national security - Kovalchuk , Veronika (Theory and Practice of Public Administration, 2026)
The article provides a comprehensive theoretical, methodological, and applied study of the specifics of strategic management of financial security as a core determinant of the general system of ensuring Ukraine’s national security under the conditions of unprecedented exogenous and endogenous shocks of the war and post-war periods. It is substantiated that the modern paradigm of public administration in this area requires a fundamental transformation from reactive tools of operational response to existing threats to proactive strategic management based on the preventive minimization of fiscal, monetary, currency, and debt risks. The architecture of the modern public management system of financial security is defined, which includes regulatory, institutional-organizational, and control-regulatory subsystems. An in-depth structural and functional analysis of the activities of key public authorities – the Ministry of Finance of Ukraine, the National Bank of Ukraine, the Bureau of Economic Security of Ukraine, the State Tax and State Customs Services, as well as the Accounting Chamber – was conducted. The level of their institutional readiness is identified, and desynchronization in the processes of managerial decision-making is detected. The author’s conceptual model for the modernization of public administration activities is proposed, based on the integration of risk-oriented monitoring and the introduction of comprehensive macro-financial stress testing. A package of specific regulatory changes to the Budget Code of Ukraine is justified (the introduction of Article 21-1 on mandatory stress testing during the preparation of the Budget Declaration) and to the Law of Ukraine "On National Security of Ukraine" (the inclusion of the Ministry of Finance and the NBU among the subjects of the security and defense sector and the creation of the Situational Analytical Center for Macro-financial Security under the National Security and Defense Council of Ukraine).